2020
DOI: 10.1002/jso.25846
|View full text |Cite
|
Sign up to set email alerts
|

Higher lymph node harvest in patients with a pathologic complete response after neoadjuvant therapy for esophageal cancer is associated with improved survival

Abstract: Background and Objectives Lymph node harvest during esophagectomy has been associated with improved survival for esophageal cancer but the value of enhanced lymph node harvest following complete pathologic response (pCR) is debated. This study investigated if increasing lymph node harvest in esophageal cancer patients with a pCR after neoadjuvant therapy and esophagectomy is associated with improved survival. Methods We queried the National Cancer Data Base for patients with esophageal cancer between 2004 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
11
2
Order By: Relevance
“…Additionally, studies have shown that lymph node harvest during esophagectomy is associated with improved postoperative survival. A study by Lutfi et al [ 26 ] demonstrated that during lymphadenectomy, when 7 lymph nodes were harvested, OS improved significantly, and when 25 Lymph nodes were harvested, it showed maximum OS benefits. Other researchers also came to a similar conclusion regarding the influence of lymphadenectomy on postoperative survival after neoadjuvant therapy; when the number of lymph node dissections reached 25, postoperative life expectancy was the highest[ 27 ].…”
Section: Surgery: Remains the Mainstay Of Treatmentmentioning
confidence: 99%
“…Additionally, studies have shown that lymph node harvest during esophagectomy is associated with improved postoperative survival. A study by Lutfi et al [ 26 ] demonstrated that during lymphadenectomy, when 7 lymph nodes were harvested, OS improved significantly, and when 25 Lymph nodes were harvested, it showed maximum OS benefits. Other researchers also came to a similar conclusion regarding the influence of lymphadenectomy on postoperative survival after neoadjuvant therapy; when the number of lymph node dissections reached 25, postoperative life expectancy was the highest[ 27 ].…”
Section: Surgery: Remains the Mainstay Of Treatmentmentioning
confidence: 99%
“…The extent of lymph node resection has been widely discussed in the field of esophageal surgery. [7][8][9] Its influence on long-term survival is also of great interest in lung cancer surgery.…”
Section: Reply: the Continued Debate On Robotic Segmentectomy-agree To Disagree Reply To The Editormentioning
confidence: 99%
“…Several clinical trials have demonstrated that neoadjuvant chemoradiotherapy can improve long-term survival and reduce locoregional cancer recurrence (4,5). Approximately 30% of oesophageal cancer patients will have a pathological complete response (pCR) after neoadjuvant chemoradiotherapy, and these patients will benefit more from neoadjuvant chemoradiotherapy (6)(7)(8). In recent years, the question has been raised of whether surgery can be dispensed with for patients who achieve pCR.…”
Section: Introductionmentioning
confidence: 99%